The survivor strain: isolation and characterization of Phormidium yuhuli AB48, a filamentous phototactic cyanobacterium with biotechnological potential - Koch, Moritz; Noonan, Avery J. C.; Qiu, Yilin; Dofher, Kalen; Kieft, Brandon; Mottahedeh, Soheyl; Shastri, Manisha; Hallam, Steven J. (Frontiers in Bioengineering and Biotechnology, 2022)
Despite their recognized potential, current applications of cyanobacteria as microbial cell factories remain in early stages of development. This is partly due to the fact that engineered strains are often difficult to grow at scale. This technical challenge contrasts with the dense and highly productive cyanobacteria populations thriving in many natural environments. It has been proposed that the selection of strains pre-adapted for growth in industrial photobioreactors could enable more productive cultivation outcomes. Here, we described the initial morphological, physiological, and genomic characterization of Phormidium yuhuli AB48 isolated from an industrial photobioreactor environment. P. yuhuli AB48 is a filamentous phototactic cyanobacterium with a growth rate comparable to Synechocystis sp. PCC 6803. The isolate forms dense biofilms under high salinity and alkaline conditions and manifests a similar nutrient profile to Arthrospira platensis (Spirulina). We sequenced, assembled, and analyzed the P. yuhuli AB48 genome, the first closed circular isolate reference genome for a member of the Phormidium genus. We then used cultivation experiments in combination with proteomics and metabolomics to investigate growth characteristics and phenotypes related to industrial scale cultivation, including nitrogen and carbon utilization, salinity, and pH acclimation, as well as antibiotic resistance. These analyses provide insight into the biological mechanisms behind the desirable growth properties manifested by P. yuhuli AB48 and position it as a promising microbial cell factory for industrial-scale bioproduction[221, 1631].